فعالية نظام الاجور في تنمية الابداع للموارد البشرية دراسة ميدانية لمجموعة من المؤسسات الاقتصادية - ‬‫إميان‬ ‫جاليلية; ‬‫أمال ‫جودي ‬ (My University, 2018)
The aim of this study is to identify the effectiveness of the wage system in developing the creativity of the human resource in a sample of economic institutions in the city of Souk Ahras, the importance of this study is to identify the contribution of payment to stimulate employees and increase their motivation, and generate enthusiasm and desire in them, and explain that salary is the engine which motivate the human resources to perform their work with the highest efficiency, and creativity and that’s what makes the enterprise achieve competitive advantage, this study also aimed to know the different ways of encouraging creativity, we can say that providing an appropriate environment for workers and offering the suitable wages for their efforts is considered as strength point which institution can develop creative thinking of workers through it, this helps the organization to reach important achievements such as : obtaining a patent, and gaining excellence and uniqueness from other competing institutions , all that had been clarified through the conceptual framework for both wage and creativity, and then indicate the relationship between them in the institutions under study. The field study included three institutions, we used the statistical package program, the results showed that high wage levels are effective ways of motivating the employees to raise performance and creativity, and that the institutions under study had a moderately effective wage system, the results showed that there is a positive and strong correlation between salary and creativity. Therefore we conclude that in order to improve the creative capacities of the institutions under study, they must adopt an appropriate wage system. ............................................................. هدفت هذه الدراسة إلى التعرف على مدى فاعلية نظام الأجور في تطوير العمل إبداع المورد البشري في عينة من المؤسسات الاقتصادية بمدينة سوق أهراس تكمن أهمية هذه الدراسة في التعرف على مدى مساهمة الدفع في تحفيز العاملين و زيادة حافزهم، وتوليد الحماس والرغبة لديهم، وشرح أن الراتب هو المحرك الذي يحفز الموارد البشرية على أداء أعمالها بأعلى كفاءة الإبداع وهو ما يجعل المؤسسة تحقق الميزة التنافسية، كما هدفت هذه الدراسة ولمعرفة الطرق المختلفة لتشجيع الإبداع، يمكننا القول أن تقديم الطريقة المناسبة البيئة للعاملين وتقديم الأجر المناسب لجهودهم تعتبر قوة النقطة التي يمكن للمؤسسة من خلالها تنمية التفكير الإبداعي لدى العاملين من خلالها، وهذا يساعد على للوصول إلى إنجازات مهمة مثل: الحصول على براءة الاختراع، والتميز وتفردها عن غيرها من المؤسسات المنافسة، كل ذلك تم توضيحه من خلال المفهومي إطار لكل من الأجر والإبداع، ومن ثم بيان العلاقة بينهما في المؤسسات قيد الدراسة. شملت الدراسة الميدانية ثلاث مؤسسات، استخدمنا فيها برنامج الحزمة الإحصائية وأظهرت النتائج أن مستويات الأجور المرتفعة هي طرق فعالة لتحفيز الموظفين على زيادة الأجور الأداء والإبداع، وأن المؤسسات قيد الدراسة لديها أجر فعال إلى حد ما وأظهرت النتائج أن هناك علاقة إيجابية وقوية بين الراتب والوظيفة إِبداع. ولذلك نستنتج أنه من أجل تحسين القدرات الإبداعية للمؤسسات قيد الدراسة، يجب عليهم اعتماد نظام مناسب للأجور. الكلمات المفتاحية: نظام الأجور، الإبداع، التحفيز، المؤسسات الاقتصادية.